Effects of 1-MHz Ultrasound on Epaxial Muscle Temperature in Horses - Adair, Henry S.; Levine, David (Frontiers in Veterinary Science, 2019)
Objective: The purpose of this study was to examine the tissue temperature changes that occur at various depths during 1.0-MHz ultrasound (US) treatments of the epaxial muscles in horses. Animals: Ten healthy adult mares with no lameness or orthopedic disease weighing between 465 and 576 kg were studied. Procedures: Two 1.0 MHz US treatments, one at an intensity of 1.0 W/cm2 and one at 2.0 W/cm2, were administered to the epaxial region. Needle thermistors were inserted in the epaxial muscles below the skin surface at depths of 1.0, 3.0, and 5.0 cm, directly under the US treatment area. Depths were verified with diagnostic ultrasound. Both intensities of US treatment were performed on each horse over a 20 cm2 area for 10 min using a sound head with an effective radiating area of 10 cm2. Treatments were administered in random order. Tissue temperature was measured before, during, and for an additional 10 min after the end of US treatment. Mean temperatures for each time point, location, and intensity was recorded at 30 s intervals. A mixed model analysis of variance (ANOVA) with repeated measures was used to test for differences in these means. Individual differences in the means was tested for by a Least Significant Difference (LSD) mean separation test. Results: At the completion of the 10 min US treatment, the temperature rise at an intensity of 1.0 W/cm2 was 1.55°C at the 1.0 cm depth, 1.18°C at 3.0 cm depth, and 1.29°C at 5.0 cm depth. At an intensity of 2.0 W/cm2, temperatures rose 2.48°C at the 1.0 cm depth, 1.24°C at 3.0 cm depth, and 1.95°C at 5.0 cm depth. Conclusion and Clinical Importance: The main findings of the study is that use of therapeutic ultrasound with a 1.0 MHz US for 10 min in horse's epaxial muscles when clipped creates the greatest heat at 1.0 cm. The heat in the tissues at 5 cm depth is more than at 3 cm depth.